‘Do not be Deteriorated by service failures, Learn from them and start managing it’: Conditions and mechanisms for managing online service failures - Manu, C; Sreejesh, S (Journal of retailing and consumer services, 2024)
Online consumers rely on two hospitality channels, direct websites and online travel agents (OTAs), to search for and book hospitality services. Although these online service channels improve service delivery efficiency, service failures have become common and unavoidable. Although online service failures and recovery efforts have received significant research attention, studies have ignored whether customer evaluations following a service failure differ based on the type of failure (informational, functional, or system) occurring in different online service booking channels (direct or OTA). Additionally, despite the significance of customer participation in service recovery, no research has examined the suitability of different recovery types based on varying levels of customer participation, such as firm, joint, and customer recovery. Thus, utilising three between-subjects experiments, this study demonstrated that information failures are more detrimental in a direct channel, whereas functional failures are more harmful to OTAs. However, system failures affect both platforms equally. The results also revealed that firm recovery is most appropriate when an information failure occurs in a direct channel. Joint recovery is suitable for functional failures in OTAs, while customer recovery is sufficient to rectify system failures. Finally, customer expectations (outcome, process, and cost) drive these positive outcomes. This research offers unique contributions to the literature and managerial practice on online service failure and recovery.